Analysis of methods for determining of static wood hardness - Космач, Олександр Павлович; Кадик, Андрій Віталійович (Eastern-European Journal of Enterprise Technologies, 2014)
Reliable determination of materials hardness, including different types of wood plays an important role in study of processes that are associated with manufacture of products, strength, stability, thermal conductivity, sound insulation, etc. Inconsistency of measurements results of static wood hardness, as well as their different units of measurement in many countries around the world raises a number of questions about the appropriateness of particular method of measurement in laboratory and industrial applications. In this regard, based on the scientific literature identified the main advantages and disadvantages of existing techniques and their comparison was shown. To eliminate the subjectivity in the comparison of measurement methods were used decision-making, in particular the prioritization method, and the method of hierarchy analysis. In this paper, we have shown the main challenges and issues that don’t allow using of considered methods. Was shown generalized classification of existing main methods of determining the hardness of the wood, which includes a number of methods based on subjective assessment of the measurement results. Using the method of prioritizing it possible to determine that preferred methods for determination of wood static hardness are the structural method, methods of Brinell and Janka. In turn, the method of hierarchical possible to determine characteristics of existing methods for determining the wood hardness, which is key during testing. Such characteristics include integrality, reliability, as well as their sensitivity. Further theoretical and experimental studies should be aimed at improving the performance of these methods characteristics at determining of wood static hardness.